UNIVERSALITY, VULNERABILITY, AND COLLECTIVE RESPONSIBILITY - Albertson Fineman, Martha (Les ateliers de l'éthique / The Ethics Forum, 2021)
Vulnerability theory as developed in the Vulnerability and Human Condition Initiative is an alternative to a rights-based or social contract paradigm for thinking about foundation concepts of state responsibility. One fundamental premise of the theory is that the individuals and groups currently described as “vulnerable populations” should not be labelled vulnerable, nor should they be sequestered in discreet categories for the purposes of law and policy. This plea for their inclusion in a larger whole is not to deny that discrimination, harm, and relative disadvantage arising from all sorts of circumstances and situations exist. Nor is it to suggest that particular instances of harm should not be addressed by appropriate state action. Rather, it is an argument that “vulnerability” is the wrong concept to use to define and isolate these groups, or any other specific group, from the whole of humanity. Human vulnerability is universal and constant, inherent in the human condition. Recognizing the theoretical mandates of accepting the universal, vulnerability theory presents a “vulnerable subject” as the only appropriate object of law and policy. This inclusive, universal legal subject incorporates the realities of the ontological body and its life-long dependence on social institutions and relationships, building a theory of essential (not voluntarily or consensual) social cohesion and reciprocity in which the state (or governing system) has the responsibility to see that these vital social institutions and relationships operate justly.